Family Disharmony and Family Resilience from a Family Sociology Perspective: A Case Study of Kasong Village, Ndoso District, West Manggarai Regency, Indonesia - Maria Vebra Lestari; Irfan Irfan; ST. Nurbayan; Anggar Putra (CV. Creative Tugu Pena, 2025)
This study aims to analyze the forms of family disharmony, identify the internal and external factors contributing to its occurrence, examine its impacts on family resilience, and interpret these findings through the perspective of family sociology using Talcott Parsons' AGIL framework. This study employed a qualitative approach with a case study design conducted in Kasong Village, Ndoso District, West Manggarai Regency. Informants consisted of five families experiencing family disharmony and several supporting informants selected through purposive sampling. Data was collected through observation, in-depth interviews, and documentation and were analyzed using the interactive model of Miles and Huberman, including data condensation, data display, and conclusion drawing. The findings reveal that family disharmony is characterized by ineffective communication, recurrent marital conflicts, verbal abuse, work-related pressures, and household financial problems. The contributing factors comprise internal factors, including poor communication, egocentric attitudes, inadequate emotional regulation, and limited understanding of family roles, as well as external factors, such as economic hardship, occupational demands, patriarchal culture, and external interference. Family disharmony adversely affects marital relationships, children's psychological and social development, family resilience, and social relationships within the community. From Talcott Parsons' structural functional perspective, these findings demonstrate that family disharmony reflects simultaneous disruptions in the four AGIL functions: Adaptation, Goal Attainment, Integration, and Latency thereby weakening the family as a social system. The novelty of this study lies in integrating the analysis of the forms, causes, and impacts of family disharmony within the AGIL framework to provide a comprehensive explanation of family resilience in rural communities.